Developing 21st Century Skills: Educational Strategies to Enhance Critical Thinking and Creativity - Nur Wahyuni (PT. Anagata Sembagi Education, 2026)
This study explores effective educational strategies for enhancing critical thinking and creativity as core competencies in 21st-century learning. These skills are essential for students to להתמודד complex problems, innovate, and actively participate in global society, yet their implementation in classroom practice remains inconsistent. This research employs a qualitative approach using a Systematic Literature Review (SLR), analyzing recent peer-reviewed journal articles from databases such as Scopus, Web of Science, and Google Scholar. Data were collected through a structured selection process based on relevance, credibility, and alignment with the research focus, and analyzed using thematic and content analysis to identify key patterns across studies. The findings reveal that instructional models such as Project-Based Learning (PjBL), Problem-Based Learning (PBL), and STEM/STEAM integration significantly enhance both critical thinking and creativity. These effects are further strengthened by constructivist principles, collaborative learning, and teacher facilitation. Additionally, technology and AI integration support critical thinking and collaboration, although their impact on creativity requires complementary pedagogical design. The study concludes that a holistic and integrated approach aligning pedagogy, learning environment, technology, and assessment is essential for effectively developing 21st-century skills.